2022
DOI: 10.3390/ijms23073822
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin-Induced Postconditioning Suppresses NMDA Receptor through Opening of the Mitochondrial Permeability Transition Pore via Melatonin Receptor in Mouse Neurons

Abstract: Mitochondrial membrane potential regulation through the mitochondrial permeability transition pore (mPTP) is reportedly involved in the ischemic postconditioning (PostC) phenomenon. Melatonin is an endogenous hormone that regulates circadian rhythms. Its neuroprotective effects via mitochondrial melatonin receptors (MTs) have recently attracted attention. However, details of the neuroprotective mechanisms associated with PostC have not been clarified. Using hippocampal CA1 pyramidal cells from C57BL mice, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…In our laboratory, ‘Safe pharmacological PostC’ represents our central concern for achieving clinical application. Diazoxide as the opener of the mito-K ATP channel is unsuitable because of its toxic side effects (Kumar et al 1976 ), while in our previous study, Furuta et al reported on the neuroprotective mechanisms of melatonin-induced pharmacological PostC (Furuta et al 2022 ) and melatonin could be a new candidate for pharmacological PostC without side effects. Thus, as future directions, in vitro and in vivo studies are needed to explore methods of delivering melatonin to the brain, such as catheterization of middle cerebral artery occlusion models.…”
Section: Discussionmentioning
confidence: 93%
“…In our laboratory, ‘Safe pharmacological PostC’ represents our central concern for achieving clinical application. Diazoxide as the opener of the mito-K ATP channel is unsuitable because of its toxic side effects (Kumar et al 1976 ), while in our previous study, Furuta et al reported on the neuroprotective mechanisms of melatonin-induced pharmacological PostC (Furuta et al 2022 ) and melatonin could be a new candidate for pharmacological PostC without side effects. Thus, as future directions, in vitro and in vivo studies are needed to explore methods of delivering melatonin to the brain, such as catheterization of middle cerebral artery occlusion models.…”
Section: Discussionmentioning
confidence: 93%
“…Detailly, Patino et al confirmed that in rat hippocampal slices exposed to OGD/R, melatonin could directly reduce the release of glutamate and prevent a persistent activation of NMDARs, thereby reducing intracellular Ca 2+ levels ( Patino et al, 2016 ). Similarly, in hippocampal slices exposed to OGD/R, melatonin reduced a surge of synaptic glutamate release and neuronal cell death after ischemia-reperfusion, which further strongly suppressed the increase in the intracellular Ca 2+ concentration by downregulating the NMDAR activity ( Furuta et al, 2022 ). Besides, in hippocampal HT22 cell lines exposed to glutamate excitotoxicity, melatonin pretreatment could prevent glutamate-mediated reduction in calcium-buffering proteins such as parvalbumin and hippocalcin and thus downregulate Ca 2+ levels ( Koh, 2012b ).…”
Section: The Mechanism Of Melatonin’s Neuroprotective Effect In Cereb...mentioning
confidence: 99%
“…Furthermore, ruthenium compounds are also known for its cytotoxicity (Alessio, 'Safe pharmacological PostC' is our central concern for clinical application, however, Diazoxide as the opener of mito-K ATP channel, is not suitable because of its toxic side effects (Kumar et al, 1976). In our previous study, Furuta.T et al reported on the neuroprotective mechanism in melatonin-induced pharmacological PostC (Furuta et al, 2022) and melatonin could be the new candidate of alternative drugs for pharmacological PostC without any side effects. Thus, for our future direction, further studies in vitro and in vivo are needed to explore ways to deliver melatonin to the brain, such as using catheter to the MCAO models.…”
Section: Pharmacological Approach To Mcumentioning
confidence: 99%